Literature Review (2020-2025): Numeracy Development and Mathematics Learning Models in Elementary Schools - Lestari, Puji; Andarani, Eka Titi; Subali, Bambang; Widiyatmoko, Arif (FKIP - Universitas Riau, 2026)
Numeracy skills are an important competency for elementary school students, but Indonesian students' numeracy achievement remains relatively low based on various assessment results. This study aims to map trends in numeracy research and mathematics learning models in elementary schools in the 2020–2025 period and identify research gaps, particularly related to the GEMBIRA Learning Model. This study used a Systematic Literature Review (SLR) approach based on the PRISMA protocol on 997 articles obtained through Google Scholar, resulting in 98 articles analyzed using content and bibliometric analysis with VOSviewer. The results show that numeracy research publications fluctuate with a significant spike in 2025, and are dominated by contextual approaches such as Realistic Mathematics Education, Ethno-RME, ethnomathematics, inquiry, and discovery learning. Bibliometric analysis indicates that numeracy and instructional models are the most dominant themes. However, no empirical studies have been found testing the implementation of the GEMBIRA Learning Model in elementary schools. These findings confirm that GEMBIRA is a potential framework but still wide open for further research.